Efficacy of congenital heart disease transition clinics in improving patient education. (3rd October 2022) - Ricci, P; Bouchard, M; Chong Zhiya, C; Constantine, A; Castro Meira, V; Gatzoulis, M; Haidu, L; Dimopoulos, K
Abstract: Background: Less than one third of adolescents with congenital heart disease (CHD) successfully complete a structured transition to adult care. Patient education is at the centre of the transition process, however, data on the impact of transition visits are limited. Purpose: To assess the efficacy of our transition clinic in educating adolescents with CHD about their cardiac condition in preparation for adult CHD care. Methods: All patients seen in our transition clinic between April 2015 and January 2022 were included. Integrated care pathways designed by the Pan London Transition Consortium guided us in the assessment and education during each of the 3 pre-planned transition visits ("ready, steady and go" model). Data collected included demographic and clinical characteristics, and qualitative assessment of the following categories: understanding, naming and describing their cardiac condition, adherence to and involvement in medication management, self-reported anxiety and awareness of the importance of dental hygiene. Results: A total of 611 patients were included in the study (age 15.1±2.3 years at the first visit, 48.1% female). 51.1% of patients attended 2 and 19.3% 3 transition consultations. Most adolescents (52.5%) had CHD of moderate complexity, whereas 28.5% had simple defects and 19% severe complexity. Learning disability (LD) was present in 19% of cases, of which 35.3% were genetic syndromes (21.6% Down Syndrome, 8.6% DiGeorge Syndrome, 2.6% Noonan Syndrome, 1.9% Sotos Syndrome, 0.9% Asperger Syndrome, 0.9% Cornelia De Lange Syndrome). The overall comprehension of their condition increased significantly in patients without LD at the second (good or excellent understanding: from 20.9% to 60.2%, p<0.0001; naming: from 19.8% to 50.2%, p<0.0001; describing: from 13.9% to 40.2%, p<0.0001) and third visit (understanding: 66.7%, p=0.043; naming: 60.4%, p=0.004, describing: 56.3%, p=0.002; Table 1). Patients with LD did not improve their knowledge over time in understanding, naming, and describing their condition between the first and second and second and third visits (all p>0.05). Adherence to and the involvement in medication management, the self-reported anxiety and awareness of the importance of dental care did not change over time (Figure 1). Conclusions: A structured transition program is an important tool in educating and supporting the delivery of care for CHD adolescents and their families prior their transition into the adult care. Our transition programme had a positive impact on comprehension in the majority of children. Adolescents with learning difficulties are a group who may benefit from more intensive or individually tailored education during transition to ensure that they are supported to understand their health needs and empowered to make their own choices where possible. Funding Acknowledgement: Type of funding sources: None.